Complement analysis 2016: clinical indications, laboratory diagnostics and quality control - Prohászka, Zoltán; Kirschfink, Michael (Immunobiology, 2016)
In recent years, complement analysis of body fluids and biopsies, going far beyond C3 and C4, has significantly enhanced our understanding of the disease process. Such expanded complement analysis allows for a more precise differential diagnosis and for critical monitoring of complement-targeted therapy. These changes are a result of the growing understanding of the involvement of complement in a diverse set of disorders. To appreciate the importance of proper complement analysis, it is important to understand the role it plays in disease. Historically, it was the absence of complement as manifested in severe infection that was noted. Since then complement has been connected to a variety of inflammatory disorders, such as autoimmune diseases and hereditary angioedema. While the role of complement in the rejection of renal grafts has been known longer, the significant impact of complement. In certain nephropathies has now led to the reclassification of some rare kidney diseases and an increased role for complement analysis in diagnosis. Even more unexpected is that complement has also been implicated in neural, ophtalmological and dermatological disorders. With this level of involvement in some varied and impactful health issues proper complement testing is clearly important; however, analysis of the complement system varies widely among laboratories. Except for a few proteins, such as C3 and C4, there are neither well-characterized standard preparations nor calibrated assays available. This is especially true for the inter-laboratory variation of tests which assess classical, alternative, or lectin pathway function. In addition, there is a need for the standardization of the measurement of complement activation products that are so critical in determining whether clinically relevant complement activation has occurred in vivo. Finally, autoantibodies to complement proteins (e.g. anti-C1q), C3 and C4 convertases (C3 and C4 nephritic factor) or to regulatory proteins (e.g. anti-C1inhibitor, anti-factor H) are important in defining autoimmune processes and diseases based on complement dysregulation. To improve the quality of complement laboratory analysis a standardization commmittee of the International Complement Society (ICS) and the International Union of Immunological Societies (IUIS) was formed to provide guidelines for modern complement analysis and standards for the development of international testing programs.